(untitled) (Journal of Medical & Health Sciences Review, 2025)
In recognition of its nutritional and biofunctional attributes, ginger (Zingiber officinale) is a spice that is used frequently around the world. The key components of ginger that enhance its food value and its bio-functional characteristics include gingerols, zingerones, and shogaols. Several diseases are currently treated with it, notably rheumatism, sore throats, arthritis, cramps, sprains, indigestion, vomiting, constipation, indigestion, hypertension, fever, and infectious infections. There are basically several kinds of ginger: dried ginger, preserved ginger, and fresh root ginger. Additionally, shogaol and gingerol have been identified due to their anti-inflammatory and antibacterial properties. Studies on cell cultures indicate the antioxidant features of ginger. It is inaccessible, therefore, if the antioxidant constituents of ginger are readily available to humans after utilization and whether they have any impact on oxidative stress markers in humans in vivo.